A catalogue of spinturnicid species (Mesostigmata: Spinturnicidae) from Brazil: distribution, host-specificity, and new locality records - Bassini-Silva, Ricardo [UNESP]; Castro-Santiago, Ana Carolina; Calchi, Ana Cláudia [UNESP]; de Mello, Érica M.; Dornelas, Leormando Fortunato; de Oliveira Viana, Amanda; Cunha, Irineu Norberto; Sabino-Santos, Gilberto; dos Santos da Silva, Allyson; Telino-Júnior, Wallace Rodrigues; Augustinho Menezes da Silva, Luiz; Soares, Gabriella; et al. (Taylor & Francis, 2024)
Spinturnicid mites are ectoparasites exclusively of bats. Herein, we provide a comprehensive catalogue of spinturnicid species recorded in Brazil focusing on their distribution nationwide. This catalogue listed 16 spinturnicid species into four different genera, and a key for the genera recorded in Brazil. Also, it provides new locality records for four species: Cameronieta almaensis Almeida, Gettinger and Gardner, Periglischrus acutisternus Machado-Allison, Periglischrus caligus Kolenati, and Periglischrus iheringi Oudemans. Additionally, this study includes a detailed discussion on the host-specificity and molecular data of these mites.
Keywords: bats; Chiroptera; ectoparasite; Mites; new records